2013
DOI: 10.1007/s10529-013-1163-0
|View full text |Cite
|
Sign up to set email alerts
|

A universal fixation method based on quaternary ammonium salts (RNAlater) for omics-technologies: Saccharomyces cerevisiae as a case study

Abstract: Genomics, transcriptomics, proteomics and fluxomics are powerful omics-technologies that play a major role in today's research. For each of these techniques good sample quality is crucial. Major factors contributing to the quality of a sample is the actual sampling procedure itself and the way the sample is stored directly after sampling. It has already been described that RNAlater can be used to store tissues and cells in a way that the RNA quality and quantity are preserved. In this paper, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…RNAlater preservation of Arabidopsis within KFTs on orbit is commonly practiced, and a facile process pathway exists for harvesting to RNAlater and frozen sample return from the ISS. RNAlaterpreserved plant materials from the ISS have been extensively used for gene expression analyses; however, to date, the use of RNAlater-preserved ISS material for proteomics has been limited to yeast (van Eijsden et al, 2013). The ability to conduct proteomics analyses on the same samples or on parallel samples returning from this established process pathway would advance the analysis potential for understanding Arabidopsis responses to spaceflight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAlater preservation of Arabidopsis within KFTs on orbit is commonly practiced, and a facile process pathway exists for harvesting to RNAlater and frozen sample return from the ISS. RNAlaterpreserved plant materials from the ISS have been extensively used for gene expression analyses; however, to date, the use of RNAlater-preserved ISS material for proteomics has been limited to yeast (van Eijsden et al, 2013). The ability to conduct proteomics analyses on the same samples or on parallel samples returning from this established process pathway would advance the analysis potential for understanding Arabidopsis responses to spaceflight.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins can be recovered from RNAlater-preserved materials (van Eijsden et al, 2013), but because the tissues and proteins are denatured, the biological properties of the subcellular components or proteins were not used to pre-separate proteins into classes such as soluble, cytoplasmic, membrane, or cell wall proteins. Therefore, the proteins identified in this study are simply considered soluble proteins according to the protocol used for their extraction.…”
Section: Protein Recovery and Identification In Spaceflight Materialsmentioning
confidence: 99%
“…Research in this direction has been conducted previously to compare different storage and preservation conditions (for example, different temperatures or preservatives such as RNALater) [ 32 , 33 ]. RNALater, a quaternary ammonium salts-based solution, is commonly used as a logistically convenient solution to preserve RNA from biological samples at room temperature when freezing is not possible, and was recently also considered for omics technologies [ 34 ]. It was shown to have a minor effect on the recovered composition and thus represents a potential alternative to immediate freezing [ 35 - 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study assessed the patterns of protein abundance in one-dimensional gels for five tissues of the gulf killifish after snap-freezing tissues in LN 2 or immersion of fresh tissues in RNAlater, showing no differences between the two methods (64) . Another study compared the quality of DNA, protein, and RNA extraction from RNAlater and snap freezing (65) . Those authors concluded that RNAlater is an excellent storage agent for yeast cells and, most likely, for other cell types and tissues, to preserve the samples for major “omics” techniques and microscopic analyses (65) .…”
Section: Resultsmentioning
confidence: 99%
“…Another study compared the quality of DNA, protein, and RNA extraction from RNAlater and snap freezing (65) . Those authors concluded that RNAlater is an excellent storage agent for yeast cells and, most likely, for other cell types and tissues, to preserve the samples for major “omics” techniques and microscopic analyses (65) .…”
Section: Resultsmentioning
confidence: 99%